Development of self-compacting strain-hardening cementitious composites by varying fly ash content. (15th September 2017) - Lin, Chang; Kayali, Obada; Morozov, Evgeny V.; Sharp, David J.
Highlights: Self-compacting SHCC were designed by adjusting matrix strength and flowability. Fly ash was used as strength modifier to fine-tune matrix strength. Self-compacting SHCC of different strength were produced. Self-compacting SHCC with high compressive strength exceeding 80 MPa was obtained. Abstract: This study investigated the role of the matrix in the production of self-compacting strain-hardening cementitious composites (SHCC). High volume fly ash pastes with desirable flowability were first designed, followed by adding micro polyvinyl alcohol (PVA) fibres to produce composite materials. The results showed that the composites were self-compacting in the fresh state, and exhibited stable multiple-cracking and strain-hardening behaviour in the hardened state. Fly ash is used not only to modify the workability of fresh mixtures, but also to adjust matrix strength to the values favourable for producing SHCC materials.